Clinical and Preclinical Evidence for a BALIMONT Multistrain Platform in Respiratory Mucosal Barrier Support - Ziraoui, Anas; Serrano, Eduardo; Devereux, Camille (International Journal of Agriculture and Food Sciences Research, 2026)
We integrated the reported BALIMONT platform data with published clinical-trial evidence relevant to respiratory mucosal immunity, upper respiratory tract infection (URTI) prevention, and gut–lung-axis signaling. The source platform combines Lacticaseibacillus rhamnosus DSM 20021, Lactobacillus acidophilus DSM 20079, and Bifidobacterium bifidum DSM 20456 with 2'-fucosyllactose, low-molecular-weight sodium hyaluronate, and baicalin across three delivery formats: mucoadhesive microcapsules, a nebulized inhalation solution, and oral enteric freeze-dried tablets. Across the retained platform dataset, 24 h respiratory epithelial adhesion reached 86.7%, 78.3%, and 72.5% for the three BALIMONT examples versus 21.6% for the comparator; respiratory secretory IgA increased by 38.9%, 32.4%, and 29.6% versus 7.5%; and 72 h microaerobic survival reached 91.3%, 87.6%, and 85.2% versus 34.7%. We then aligned these findings with published randomized trials showing that selected Lactobacillus- and Bifidobacterium-containing interventions shortened common-cold duration, reduced symptom burden, lowered school absenteeism or antibiotic use, or improved quality-of-life-related respiratory outcomes. Taken together, the evidence supports BALIMONT as a respiratory-barrier-oriented probiotic platform with plausible translational relevance, while also indicating that BALIMONT-specific randomized human validation is still needed.